Tracing racism in antiracist narrative texts online. Issue 7 (19th May 2022) - Archakis, Argiris
ABSTRACT: Τhis paper studies online narrative texts, which, despite their declared antiracist stance, reproduce racist positionings against migrants. Based on the broader framework of Critical Discourse Analysis, our main research question concerns the ways racist and antiracist positionings coexist. To this end, we employ an enriched version of Bamberg's tripartite model which distinguishes the micro-levels of narrative world and narrative interaction, from which the positionings towards the discourses of the macro-level, in the present case the national discourse, emerge. A common feature of the media narratives under study is the ambiguity between an antiracist reading and a motile racist one. In these readings the denοuncement of majority instances of illiberal/frozen racism coexist with the representation of migrants as people largely assimilated to the majority context. Due to this coexistence, such texts become vehicles of liquid racism.